Synchronous Control System Design Scheme of Vehicle Dynamic Test Platform - LI Kaiping; XIONG Jie; FAN Yiping (机车电传动)
For the test patterns conversion complexity and workers high work intensity of locomotive test, a new design scheme of synchronous control system was presented. Converter control pattern changing and optimization of synchronous gear box design method was provided, which could realized vehicle dynamic test three control modes conversion of rig control, frame control and axis control conveniently to meet the locomotive test requirements.